2018
DOI: 10.1016/j.ultsonch.2017.09.054
|View full text |Cite
|
Sign up to set email alerts
|

A novel high performance nano chemosensor for copper (II) ion based on an ultrasound-assisted synthesized diphenylamine-based Schiff base: Design, fabrication and density functional theory calculations

Abstract: A novel high selective colorimetric chemosensor was introduced based on a nano diphenyl-based Schiff base (HL), 2,2'-((1E,1'E)-(((hexylazanediyl)bis(4,1-phenylene))bis(methanylylidene))bis(azanylylidene))bis(4-methylphenol) that synthesized using sonochemical method. HL was characterized by FT-IR, MS, TGA, H NMR,C NMR, SEM and elemental analysis techniques, then fabricated as the portable strips for sensing copper (II) ions in aqueous media. The binding interaction between HL and various metal ions was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…In this work, frequency calculations were done in order to confirm the structures were true minima. [43][44][45][46] In this work, adsorption energy (E ad ) and free energy (G ad ) amounts of H 2 Se molecule on considered AlN-NCSs and AlP-NCSs were obtained via equations 1 and 2, respectively: …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, frequency calculations were done in order to confirm the structures were true minima. [43][44][45][46] In this work, adsorption energy (E ad ) and free energy (G ad ) amounts of H 2 Se molecule on considered AlN-NCSs and AlP-NCSs were obtained via equations 1 and 2, respectively: …”
Section: Computational Detailsmentioning
confidence: 99%
“…The creation of unsaturated sites on Al, P and N atoms play main roles in gas adsorption and so AlN-NCS and AlP-N-CS can be gas sensors with the highest performance. [8][9][10][11][12] The adsorptions of toxic gases with various compounds to identify the suitable sensor are important works to solve the environmental problems. In previous studies, widely in chemical processes the various nanostructures because of their sensitivity and activity have been used and results have been shown that functionalization of na-nostructure can improvement the capability of nanostructures to detect toxic gases.…”
Section: Introductionmentioning
confidence: 99%
“…Copper element is the third abundant essential transition element in living organisms (for example; human, plants, and animals) which naturally exist in water, soil, sediment, rock and air . This element due to its participation in the biological process, like enzyme hydrolysis, electron transfer, is a good catalyst for redox reactions .…”
Section: Introductionmentioning
confidence: 99%
“…The rechargeable batteries have been used in starter of car, consumer devices and battery reservoir center. [1][2][3][4][5][6] In lithium-ion battery (LIB) there are two processes; in charging process the lithium ions transferred from the positive to negative electrode and in discharge process the motion of lithium ions is the reverse of charge process. LIBs have high energy compression, high storage capacity, small memory effect and small self-evacuation.…”
Section: Introductionmentioning
confidence: 99%